Treatment of Rice Husk Ash to Improve Adsorption Capacity of Cobalt from Aqueous Solution - Gad, H.M.H.; Omar, H.A.; Aziz, M.; Hassan, M.R.; Khalil, M.H. (Asian Journal of Chemistry, 2015)
Equilibrium, kinetics and thermodynamics parameters of adsorption of cobalt using silica gel, (Si-Cl-RHA) (RHA = rice husk ash) were investigated. The sorption experimentation work were carried out at pH 6 for 2 h. It was found that the sorption process follow the model of pseudo second-order and the intra-particle diffusion was not the sole of the rate principal step. Adsorption data were perfectly described by Dubinin-Radushkevich, Langumuir and Freundlich models with a highest sorption capacity 123 mg/g according to D-R model at 25 °C which increased to 256 mg/g at 65 °C. From the calculation of the thermodynamic parameters (DG°), (DH°) and (DS°) it can be concluded that the adsorption is spontaneous, a chemical and endothermic process. The presence of phosphate anions in solution, leads to the increase of adsorbability of Co(II) ions. The regeneration and recovery of Si-Cl-RHA was achieved by 99.50 (%) using H2SO4 (0.5 M). Finally, the applicability and effectiveness of the preparations Si-Cl-RHA for removal of cobalt from simulates of low level liquid waste and process wastewater that might arise in research laboratories, show an efficiency of 93 and 99.5 % for 137Cs and 60Co removal, respectively.